2015
DOI: 10.1155/2015/785415
|View full text |Cite
|
Sign up to set email alerts
|

High-Electron-Mobility SiGe on Sapphire Substrate for Fast Chipsets

Abstract: High-quality strain-relaxed SiGe films with a low twin defect density, high electron mobility, and smooth surface are critical for device fabrication to achieve designed performance. The mobilities of SiGe can be a few times higher than those of silicon due to the content of high carrier mobilities of germanium (p-type Si: 430 cm 2 /V⋅s, p-type Ge: 2200 cm 2 /V⋅s, n-type Si: 1300 cm 2 /V⋅s, and n-type Ge: 3000 cm 2 /V⋅s at 10 16 per cm 3 doping density). Therefore, radio frequency devices which are made with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Our investigation indicates that preparation of the sapphire substrate surface plays a key role in determining the GaAs film quality. This is in agreement with previous reports that the sapphire wafer treatment before deposition of an epilayer has been effective in reducing twinning . More specifically surfaces with clear step-terraces have generally been effective in encouraging a layer-by-layer growth mode and is widely used to control both the quality and orientation of epilayer in heteroepitaxy. , To explore the role of the sapphire substrate surface on III–V growth, we investigated three different kinds of initial substrate surfaces: (a) a corrugated substrate surface with no step-terrace structure (S1); (b) a weakly defined step-terrace surface (S2); and (c) a well-defined step-terrace surface (S3).…”
Section: Resultsmentioning
confidence: 99%
“…Our investigation indicates that preparation of the sapphire substrate surface plays a key role in determining the GaAs film quality. This is in agreement with previous reports that the sapphire wafer treatment before deposition of an epilayer has been effective in reducing twinning . More specifically surfaces with clear step-terraces have generally been effective in encouraging a layer-by-layer growth mode and is widely used to control both the quality and orientation of epilayer in heteroepitaxy. , To explore the role of the sapphire substrate surface on III–V growth, we investigated three different kinds of initial substrate surfaces: (a) a corrugated substrate surface with no step-terrace structure (S1); (b) a weakly defined step-terrace surface (S2); and (c) a well-defined step-terrace surface (S3).…”
Section: Resultsmentioning
confidence: 99%
“…To reinforce that the starting surface must be relatively Sifree in order to maintain low surface roughness, prevent SiC formation, and achieve pristine graphene growth, we attempt to synthesize graphene on Si 0.15 Ge 0.85 (111) sputtered on csapphire using a published procedure. 78 Figure S1a shows a SEM micrograph of the surface after CVD at 960 °C. The surface appears rough and is interspersed with white particles, which presumably are SiC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…■ METHODS Nanoribbon Synthesis. Ge/Si(001) (3 μm) and Si 0.15 Ge 0.85 (111) (fabricated using published procedures 55,78 ) and undoped Ge(001) (purchased from Wafer World, part #1459) substrates were loaded into a horizontal quartz tube furnace in which the furnace can slide over the length of the tube. Prior to nanoribbon synthesis, the CVD chamber was evacuated to <10 −2 Torr using a scroll pump.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Saini et al showed that among all other multi-gate architectures, triple gate junctionless devices exhibit superior gate controllability [11-14].Recently, gate-all-around nanowire has become a promising architecture for scaling of MOSFETs [15,16].In this paper, we compare two junctionless multi-gate (JLMG) architectures: junctionless gate-all-around (JL-GAA) and junctionless triple gate (JLTG) each with different high-κ gate oxides to further improve the gate control. These devices derive the advantage of high mobility of Silicon-Germanium material (1538 cm 2 /V • s at 6 × 10 17 cm −3 doping) [17]. Section 2 explains the structure and simulation of these devices.…”
mentioning
confidence: 99%
“…In this paper, we compare two junctionless multi-gate (JLMG) architectures: junctionless gate-all-around (JL-GAA) and junctionless triple gate (JLTG) each with different high-κ gate oxides to further improve the gate control. These devices derive the advantage of high mobility of Silicon-Germanium material (1538 cm 2 /V • s at 6 × 10 17 cm −3 doping) [17]. Section 2 explains the structure and simulation of these devices.…”
mentioning
confidence: 99%